Erratum: Development of an Android-Based “LaporKPS” Application to Support the Service Center for Reports of Sexual Violence and Harassment Cases - Editor, (Data Science: Journal of Computing and Applied Informatics, 2023)
There is a correction in the writing of the author's name in this publication due to technical errors of the editor. The published article and Web Metadata: Adhim Bagas Wisnu Aji1, Eko Sipraptono2 Correction: Adhim Bagas Wisnu Aji1 and Eko Supraptono2 Date of Correction: May 19, 2023 Status: Reupload as an online publication